2006
DOI: 10.4049/jimmunol.176.10.5988
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Regulatory Cell Induction and Function in Transplant Recipients after CD154 Blockade Is TLR4 Independent

Abstract: Although the role of CD4+ T regulatory cells (Treg) in transplantation tolerance has been established, putative mechanisms of Treg induction and function in vivo remain unclear. TLR4 signaling has been implicated in the regulation of CD4+CD25+ Treg functions recently. In this study, we first examined the role of recipient TLR4 in the acquisition of operational CD4+ Treg following CD154 blockade in a murine cardiac transplant model. Then, we determined whether TLR4 activation in allograft tolerant recipients wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…By contrast, the acute rejection models of skin and heart transplantation are dependent mainly on T-cell function, because depletion of these cells prevented rejection (Zhai et al, 2006). In addition to the lower total numbers of DCs, the intragraft DCs showed a less mature phenotype, which has been observed previously in the draining lymph nodes of animals that have received skin transplants, in conjunction with a lower number of anti-graft-reactive T cells and diminished Th1 immunity (Goldstein et al, 2003).…”
Section: Research Articlementioning
confidence: 83%
“…By contrast, the acute rejection models of skin and heart transplantation are dependent mainly on T-cell function, because depletion of these cells prevented rejection (Zhai et al, 2006). In addition to the lower total numbers of DCs, the intragraft DCs showed a less mature phenotype, which has been observed previously in the draining lymph nodes of animals that have received skin transplants, in conjunction with a lower number of anti-graft-reactive T cells and diminished Th1 immunity (Goldstein et al, 2003).…”
Section: Research Articlementioning
confidence: 83%
“…Primers used to amplify a specific mouse gene fragments have been published. 7,15 Statistical Analysis. Results are shown as mean Ϯ standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that loss of costimulatory signals, which are common to B cells and other APCs, results in the conversion of CD4 ϩ effector T cells toward a more regulatory population due to induction of anergy or up-regulation of FoxP3 (45,46). Also, B cell expansion blocks T cell regulatory activity, suggesting that depletion of B cells could expand a regulatory T cell population (47).…”
Section: Discussionmentioning
confidence: 99%